The Influence of Company Reputation on Customer Loyalty in Indonesian Commercial Banks: The Mediating Role of Country of Origin in the Perspective of Signaling Theory - Muhammad Nadif Kurniawan; Adi Setiawan (Interdisciplinary Social Studies, 2026)
This study aims to analyze the impact of company reputation on the customer loyalty of commercial banks in Indonesia from the perspective of signal theory, as well as evaluate the role of the country of origin as a mediating variable in the relationship. Data was obtained from 61 commercial bank customers at Bank BJB KC Swadaya Gunung Jati University Cirebon using quantitative research methods. A company's reputation is defined as a multidimensional construct that includes corporate social responsibility (CSR), relationship marketing, product quality, and corporate responsiveness. The data were analyzed using structural equation (SEM) model-based path analysis with the help of AMOS software. The results of the study show that corporate social responsibility signals do not directly affect customer loyalty, but indirectly affect significantly through the country of origin, which indicates full mediation. Product quality has been shown to have a direct and significant influence on customer loyalty, and is the most influential factor in the research model. In contrast, relational marketing and company credibility did not show significant influence. The research model can explain 60.9% variation in customer loyalty. The study confirms that a company's reputation serves as a strategic signal, the effectiveness of which depends on the type of signal being sent and the context of the bank's country of origin. These results expand the application of signal theory in Indonesia's banking sector and provide important implications for bank reputation management in building sustainable customer loyalty.